Current challenges in agricultural water resource development and management in the Philippines - Inocencio, Arlene B. (Animo Repository, 2018)
There is a growing concern in the Philippines and elsewhere over what some have termed a “water crisis”—too little or at times too much water. We first discuss the historical context of Philippine irrigation development and management. Then we discuss the trends in irrigation development—public and private investment, national and communal systems, and new and rehabilitation projects. We note the rapid increase in private investment based on the agricultural census, mostly pumps and shallow tube wells, and the increase in investments on communals in the last decade. With the recurring and persistent problems on planning and investment, design and management, and operation and maintenance, we call for the rethinking of the way we develop and manage our agricultural water resources. Despite all the concerns, there are paths to improving water management and increasing water productivity, some of which are currently being pursued. We conclude, however, that climate change will make it difficult to achieve food security without continued reliance on rice imports. © 2018 by De La Salle University.